(untitled) (Research, Society and Development, 2021)
Introduction: Acquired immunodeficiency syndrome (AIDS) is caused by the human immunodeficiency virus (HIV), which attacks the immune system and can reduce an infected person’s ability to resist other infections and diseases. It is estimated that more than 50% of individuals affected with HIV are susceptible to developing HIV-associated neurocognitive decline. Objective: to explore, through an integrative literature review, the structural changes in the brain and cognitive decline in HIV patients. Search methodology: this is a descriptive research of the narrative literature review type, through online access in the PubMed, Scielo, CDSR, Google Scholar, BVS and EBSCO databases, in September 2021. Discussion: AIDS it can manifest as a subcortical dementia, which manifests itself as a significant loss in the capacity for attention and concentration, depressive symptoms and motor alterations in relation to the speed and precision of performing different tasks. This syndrome is associated with pathological changes in the brain that include generalized atrophy, white matter changes causing leukoencephalopathy, microglial nodules typical of viral encephalitis, and multinucleated giant cells, which appear to be directly infected with HIV. Final considerations: although the HIV virus is recognized for its direct effect on the cellular immune system through the depletion of CD4 T lymphocytes, the virus is also still associated with broad effects on the nervous system, including a direct effect on the brain, spinal cord and peripheral nerves.